Spin and wavelength multiplexed nonlinear metasurface holography - Ye, Weimin; Zeuner, Franziska; Li, Xin; Reineke, Bernhard; He, Shan; Qiu, Cheng-Wei; Liu, Juan; Wang, Yongtian; Zhang, Shuang; Zentgraf, Thomas (Nature Communications)

Rotational Doppler effect in nonlinear optics - Li, Guixin; Zentgraf, Thomas; Zhang, Shuang (Nature Physics)

Designermaterialien für nichtlineare Optik - Probst, Heike; Zentgraf, Thomas (Physik in unserer Zeit)

Giant Nonlinear Optical Activity of Achiral Origin in Planar Metasurfaces with Quadratic and Cubic Nonlinearities - Chen, Shumei; Zeuner, Franziska; Weismann, Martin; Reineke, Bernhard; Li, Guixin; Valev, Ventsislav Kolev; Cheah, Kok Wai; Panoiu, Nicolae Coriolan; Zentgraf, Thomas; Zhang, Shuang (Advanced Materials)

Symmetric Anonymous Credentials with Protocols for Relations on Attributes - Hamm, Julian

Helicity-Preserving Omnidirectional Plasmonic Mirror - Xiao, Shiyi; Mühlenbernd, Holger; Li, Guixin; Kenney, Mitchell; Liu, Fu; Zentgraf, Thomas; Zhang, Shuang; Li, Jensen (Advanced Optical Materials)

Supporting Business Model Idea Generation Through Machine-generated Ideas: A Design Theory - John, Thomas (Proceedings of the 37th International Conference on Information Systems (ICIS), Dublin, Ireland)
Successful business model innovation is impossible without innovative business model ideas. When generating such ideas, humans make use of two properties of the human cognitive system: First, their ability to build up knowledge (i.e., raw material for new ideas), and second, their ability to flexibly recombine that knowledge. While these properties enable humans to generate innovative ideas, the amounts of knowledge and cognitive flexibility that humans can possess are limited, which in turn limits human idea generation capability. With business model idea generators, a new class of information systems is proposed that can contribute to alleviating the limits that constrain human idea generation. The ideas that such idea generators produce can complement human business model ideas, thereby increase the probability for high-quality ideas, and eventually raise the odds of successful business model innovation. The contribution is a design theory that describes the architecture of the proposed idea generators.

UTCNN: a Deep Learning Model of Stance Classification on Social Media Text - Chen, Wei-Fan; Ku, Lun-Wei (Proceedings of COLING 2016, the 26th International Conference on Computational Linguistics)

WordForce: Visualizing Controversial Words in Debates - Chen, Wei-Fan; Lin, Fang-Yu; Ku, Lun-Wei (Proceedings of COLING 2016, the 26th International Conference on Computational Linguistics: System Demonstrations)

Chinese Textual Sentiment Analysis: Datasets, Resources and Tools - Ku, Lun-Wei; Chen, Wei-Fan (Proceedings of COLING 2016, the 26th International Conference on Computational Linguistics: Tutorial Abstracts)